2021
DOI: 10.3390/molecules26103011
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Attenuated Neurotoxicity in Sporadic Animal Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases leading to dementia. Despite research efforts, currently there are no effective pharmacotherapeutic options for the prevention and treatment of AD. Recently, numerous studies highlighted the beneficial effects of curcumin (CUR), a natural polyphenol, in the neuroprotection. Especially, its dual antioxidant and anti-inflammatory properties attracted the interest of researchers. In fact, besides its antioxidant and anti-inflammatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Curcumin is one of the natural phytochemicals in turmeric and is a potent anti-amyloidogenic agent which has been found to effectively disaggregate Aβ species directly, which in turn hinders the formation of fibrils and oligomers and improves cognitive performance [20,21]. In addition, curcumin attenuated the oxidative stress in a streptozotocin (STZ)-induced model by enhancing reduced glutathione (GSH) content and reducing the acetylcholinesterase activity in the hippocampus and cerebral cortex [22,23]. Previous studies showed that curcumin increased lifespan and decreased amyloid neurotoxicity in an invertebrate model [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is one of the natural phytochemicals in turmeric and is a potent anti-amyloidogenic agent which has been found to effectively disaggregate Aβ species directly, which in turn hinders the formation of fibrils and oligomers and improves cognitive performance [20,21]. In addition, curcumin attenuated the oxidative stress in a streptozotocin (STZ)-induced model by enhancing reduced glutathione (GSH) content and reducing the acetylcholinesterase activity in the hippocampus and cerebral cortex [22,23]. Previous studies showed that curcumin increased lifespan and decreased amyloid neurotoxicity in an invertebrate model [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Current approved therapies against MS reduce relapse rates, but they do not promote myelin repair nor do they prevent or reverse disease progression. Since we showed that curcumin treatment promotes neuroprotection in animal models [ 23 , 24 ], we considered that curcumin treatment may promote neuroprotection in MS animal models, which could be regulated by several mechanisms. In fact, in the present study, curcumin demonstrated a dual mechanism of action: (i) an immunomodulatory effect, through an anti-inflammatory effect in reactive astrocytes and the inhibition of immune cells’ infiltration into the spinal cord, and (ii) an ameliorating effect of myelination through the elevation of MBP expression in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, curcumin (Cur), from Curcuma longa [ 20 ], was reported to have multiple advantageous effects, including antioxidant [ 21 ] and anti-inflammatory ones [ 22 ]. In addition, the efficiency of Cur against several inflammatory diseases such as neurodegenerative diseases [ 23 , 24 ] and cancer [ 25 ] has been highlighted in previous studies. In the present work, we investigated the potential therapeutic effect of curcumin on autoimmune (EAE) and toxic (cuprizone) animal models of MS, as well as on an inflamed astrocyte cell line culture.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of curcumin significantly decreased MDA level and increased the activity of SOD and catalase enzyme in the hippocampus of AD rats. Further, curcumin attenuated the neurodegeneration and decline of recognition memory in the AlCl 3 -treated AD rats ( ELBini-Dhouib et al, 2021 ; Table 2 ).…”
Section: Role Of Natural Bioactive Compounds In the Recovery Of Age-a...mentioning
confidence: 96%